The Insolvency Regime for Large Enterprises in Italy : An Economic and Legal Assessment - Belhocine, Nazim; Garcia-Macia, Daniel; Garrido, Jose. (Washington, D.C. : International Monetary Fund, 2018)
The modernization of Italy's insolvency framework has been the subject of much interest in recent years, related not least to its role in potentially facilitating an efficient allocation of resources. A unique feature of Italy's insolvency framework is a special regime for large enterprises known as 'extraordinary administration'. This paper evaluates the merits of this special regime by assessing its efficacy and success in achieving its stated goals and comparing its features to international standards and best practices. It finds that the special regime tends to impose large costs on creditors and the state. The regime results, in most cases, in the sale of parts of the group, followed by a liquidation phase of the remaining assets which can take longer than the general regime, hindering legal certainty for creditors and more generally economic efficiency, investment and job creation. Based on international best practices and experience, consideration should be given to folding the special regime into the general insolvency regime, possibly with provisions to allow for state intervention in specific well-defined circumstances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Bankruptcy; Liquidation